2015
DOI: 10.1111/iju.12716
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of visceral obesity in patients with advanced renal cell carcinoma undergoing nephrectomy

Abstract: Results: High visceral fat area (greater than 50 percentiles in each sex) was associated with longer cancer-specific survival (P = 0.01) or overall survival (P = 0.03), whereas visceral fat area/subcutaneous fat area ratio showed no influence on survival outcomes. By multivariate analysis adjusted with clinicopathological variables, low visceral fat area was an independent predictor of cancer-specific death and overall death (cancer-specific survival P = 0.004, hazard ratio = 2.19; overall survival P = 0.003, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…This result is consistent with Antoun et al who reported that a high amount of subcutaneous adipose tissue independently and significantly associates with longer survival in 120 prostate cancer patients (Antoun et al , 2015). Controversy remains regarding the association between visceral adiposity and cancer survival as visceral adipose tissue is reported to be associated with poorer survival in patients with hepatocellular carcinoma (Fujiwara et al , 2015) or with better prognosis (Kaneko et al , 2015; Lee et al , 2015) in advanced renal cell carcinomas. Adiposity variables such as visceral to subcutaneous adipose tissue ratio have been applied in previous studies (Fujiwara et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is consistent with Antoun et al who reported that a high amount of subcutaneous adipose tissue independently and significantly associates with longer survival in 120 prostate cancer patients (Antoun et al , 2015). Controversy remains regarding the association between visceral adiposity and cancer survival as visceral adipose tissue is reported to be associated with poorer survival in patients with hepatocellular carcinoma (Fujiwara et al , 2015) or with better prognosis (Kaneko et al , 2015; Lee et al , 2015) in advanced renal cell carcinomas. Adiposity variables such as visceral to subcutaneous adipose tissue ratio have been applied in previous studies (Fujiwara et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing the effect of adiposity, either visceral or subcutaneous, on cancer survival have yielded inconsistent results (Rickles et al , 2013; Fujiwara et al , 2015; Kaneko et al , 2015; Lee et al , 2015). Small sample sizes, lack of cancer-specific cut offs associated with survival, exclusion of conventional or body composition variables associated with survival in multivariate analysis as well as focusing on short- or long-term mortality as an outcome contribute to inconsistent results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, body composition, including adipose tissue and skeletal muscle, can be directly evaluated using CT imaging, especially in the surgical field. Although recent studies have shown that a higher visceral fat area (VFA) evaluated using CT imaging was significantly associated with poor survival in several cancers [42][43][44][45][46], the association between VFA and prognosis remains controversial [47][48][49]. Our previous study also evaluated the VFA for a definition of visceral obesity, and obesity was considered present when the VFA was ≥100 cm 2 in both males and females [50].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of multiple Japanese studies, visceral obesity rather than BMI may be a more useful predictor of disease-recurrence survival rather than BMI since high visceral fat has been associated with longer cancer-specific survival and overall survival. [48][49][50] Multiple mechanisms linking obesity to increased risk of RCC have been proposed. Adipose tissue secretes molecules known as adipokines into the blood stream, which play a role in energy balance, macromolecule metabolism, Kabaria et al and signaling to the rest of the body.…”
mentioning
confidence: 99%